Privatisation and public enterprise : Asia pacific experience / edited by Geeta Gauri - "Gauri, Geeta" (New Delhi, 1991)
Privatisation in the Asia - Pacific region has been dynamic and innovative. Without a formal garb privatisation has been occuring in unique ways and in unlikely places.It was only through the initiation of the Aian and Pacific Developments Centre that systematic effort was made to streamline and document the evidence. In the process the term 'privatisation' has widened to encompass any roll back of direct state intervention in economic activity. This more realistic definition enabled an enquiry into the dynamic changes taking place in the region. The book is a documentary evidence of this dynamism.
Keywords: Privatisation